1-methylcyclopropene (1-MCP) application increases post-harvest storage of pears - Pasa, Mateus da Silveira (2018)
One of the strategies to maintain fruit quality and increase storage time of climacteric fruit such as pear is the use of 1-methylcyclopropene (1-MCP), reducing the effects of ethylene, which is the main responsible for fruit ripening. The aim of this study was to evaluate the influence of 1-MCP on post-harvest fruit quality of ‘Abate Fetel’, ‘Packham’s’ and ‘Tenra’ pears in regular air cold storage. The fruit were treated with 1-MCP inside sealed plastic boxes at 20 ºC, for 14 hours, and then transferred to cold storage (0 °C ± 1 °C; 85% ± 5% UR), where they were kept during 30, 60, 90, and 120 days. The assessed parameters were flesh firmness, DA index, pH of juice, titratable acidity and soluble solids. It was observed that 1-MCP was efficient in maintaining fruit flesh firmness of the studied cultivars kept in cold storage. Also, the degradation of chlorophyll in fruits of ‘Abate Fetel’ and ‘Packham’s’ pear was reduced with 1-MCP application.